1988
DOI: 10.1007/bf00437430
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopiazonic acid in combination with aflatoxins, zearalenone and ochratoxin A in Indonesian corn

Abstract: The mycotoxin, cyclopiazonic acid (CPA), was detected at concentrations as high as 9 ppm in 21 of 26 corn samples from a Bogor poultry feedmill. This is the first demonstration of the natural occurrence of CPA in Indonesia. CPA was always accompanied by other mycotoxins, especially aflatoxins, suggesting that the interactive toxicity of these mycotoxins to poultry should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…Of 17 samples, three (17.6%) were contaminated in the range from 6.6 to 61.9 lg/kg. The result is lower than reported by Widiastuti, Maryam, Blaney, Stoltz, and Stoltz (1988a) who detected 11 (21%) of 52 samples of maize for feed from Bogor (western Java, Indonesia) to be contaminated in a large range from 1 to 13,500 g/kg, and by Widiastuti et al (1988b) who detected seven of 16 samples from the same region in a range from 1 to 14 lg/kg. Salay and Mercadante (2002) reviewed contamination of mycotoxins in maize from several regions in Brazil and noted that more than 2000 samples in six regions, ranging from 0% to 52.3% of samples, were contaminated by ZON with the maximum level ranging from 3 to 4987 lg/kg.…”
Section: Analyses With Elisa Methods and Occurrence Of Zon In Samplescontrasting
confidence: 84%
See 1 more Smart Citation
“…Of 17 samples, three (17.6%) were contaminated in the range from 6.6 to 61.9 lg/kg. The result is lower than reported by Widiastuti, Maryam, Blaney, Stoltz, and Stoltz (1988a) who detected 11 (21%) of 52 samples of maize for feed from Bogor (western Java, Indonesia) to be contaminated in a large range from 1 to 13,500 g/kg, and by Widiastuti et al (1988b) who detected seven of 16 samples from the same region in a range from 1 to 14 lg/kg. Salay and Mercadante (2002) reviewed contamination of mycotoxins in maize from several regions in Brazil and noted that more than 2000 samples in six regions, ranging from 0% to 52.3% of samples, were contaminated by ZON with the maximum level ranging from 3 to 4987 lg/kg.…”
Section: Analyses With Elisa Methods and Occurrence Of Zon In Samplescontrasting
confidence: 84%
“…In Indonesia, a tropical and relatively humid country, information on ZON contamination of maize-based foods is still rare. In a one-year survey of maize for feed in Bogor, west region of Indonesia, Widiastuti, Maryam, Blaney, Stoltz, and Stoltz (1988b) reported that zearalenone was detected in 21% of 52 samples in a large range from 1 to 13,500 lg/kg. Further investigation found that out of 16 maize samples collected from Central Java, two samples were contaminated by zearalenone at a level of 11 and 12 lg/kg, respectively (Ali, Sardjono, Yamashita, & Yoshizawa, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…In another report, 21/26 samples of Indonesian corn contained 0.12-9.22 ppm of CPA, with more than 50% greater than 1 ppm. Co-existence of AF (25/26), zearalenone (7/26) and ochratoxin (1/26) was also reported [10]. CPA was reported to occur to the extent of 0.25 ppm in 4 of 7 truck loads of At r (0.508 ppm) contaminated maize [11].…”
Section: Resultsmentioning
confidence: 68%
“…Urano et al [ 12], reported that 51% of 45 corn samples were contaminated with CPA (<0.025-2.8 ppm) and 87% of them contained AF (0.001-2.3 ppm). Earlier studies on maize [9][10][11][12] showed a prevalence rate of 51-100% with a maximum level of 10 ppm and almost all the samples contained AF. In the present study, a prevalence rate of 38% was found in maize with a maximum level of 12 ppm.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation